Internal carotid plexus schwannoma of the cavernous sinus: Case report - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
OBJECTIVE AND IMPORTANCE: Schwannomas of the central nervous system usually originate from the vestibular nerve and occasionally originate from the trigeminal, nerve. Sympathetic plexus schwannomas are extremely rare and have never been noted within the cavernous sinus. CLINICAL PRESENTATION: A 23-year-old man experienced occasional double vision for a period of 6 months. Magnetic resonance imaging studies revealed an isointense lesion, with enhancement after gadolinium administration, located inferomedial to the internal carotid artery within the left cavernous sinus. INTERVENTION: We explored the cavernous sinus via a left-sided extraduralpterional approach and found the tumor inferomedial to the cavernous segment of the internal carotid artery. Microsurgical gross total resection of the tumor was performed. The IIIrd (oculomotor) to Vlth (abducens) cranial nerves within the cavernous sinus were not related to the tumor and were preserved. The operative findings and the. anatomic location of the tumor demonstrated that it originated from the internal carotid plexus within the cavernous sinus. The patient's postoperative course was uneventful, and he exhibited no cranial nerve deficits. However, incomplete Horner's syndrome was present on the treated side. CONCLUSION: We present the first reported case of an internal carotid plexus schwannoma, and we describe in detail its anatomic and neuroradiological characteristics-The microneurosurgical resection of this unusual tumor within the cavernous sinus was successful and without morbidity.
Keywords: cavernous sinus; internal carotid plexus; pterional-extradural approach; schwannoma; 6TH CRANIAL NERVES; SYMPATHETIC PATHWAYS; TRIGEMINAL NEURINOMAS; PETROUS APEX; CONNECTIONS; NEUROMAS; ANATOMY; TUMORS; SERIES